Біографії членів Новозибківського та Чернігівського земляцтв студентів Київського комерційного інституту як джерело до реконструкції «портрету» молоді Чернігівщини початку XX ст. - Чуткий, А. (Сiверянський лiтопис, 2019)
На основі архівних документів, які вперше вводяться до наукового обігу, реконструюються біографії вихідців з Чернігівщини, котрі на початку XX ст. навчались у
Київському комерційному інституті.
В етнічному відношенні показовим було спрямування на здобуття економічної освіти
вихідців з єврейської громади краю, що підтверджує особливу роль євреїв в економічному
житті України початку XX ст. При цьому виявляється міграція євреїв між сусідніми
білоруськими землями і Чернігівщиною.
У випадку українців, що походили з Чернігівщини, показовим є вступ на навчання до
цього економічного вишу вихідців з православного духовенства. On the basis of archival documents, which were first introduced into scientific circulation,
biographies of immigrants from Chernihiv region, who studied at Kyiv Commercial Institute
at the beginning of XX century, were reconstructed.
As it was the first national higher educational institution of economic profile, it allowed
to «show» a tendency to move to the sphere of economic activity immigrants from different
population groups of Chernihiv region; as well as the degree of connection of this region of
Ukraine with Kyiv at that stage of history. Ethnically, the orientation towards obtaining economic
education of immigrants from the Jewish community of the region was indicative, which
confirms the special role of Jews in the economic life of Ukraine at the beginning of the XX
century. At the same time, the migration of Jews between the neighboring Belarusian lands
and Chernihiv region is revealed.
In case of Ukrainians who came from Chernihiv region, the entry into this economic university
of Orthodox clergy is significant. It testified to both the secularization of worldview
and the crisis of religiosity, in particular, among young people, which, by virtue of its mass,
testified to the approaching global political turmoil (as a result of the monopoly of Orthodoxy
destruction, which was one of the foundations of autocracy, in the worldview system of the then
society), which happened soon. This is also indicated by the facts of the particular activity of
the student youth in political and anti-social actions. And this, in turn, was evidenced by the
fact that the student body was at the forefront of all processes in the then society, especially
keenly sensing and responding to the changes that were ripening in it. At the same time speaking
for the radical way of their decision. Therefore, it is only natural that the political power that
was able to especially drag the largest percentage of this category to its side, was also largely
judged by the victory in the struggle for power in the imperial space. And as it known that such
a political force was the all-Russian left-wing parties.